FACTORS AFFECTING THE UTILIZATION OF VOLUNTARY COUNSELING AND TESTING (VCT) SERVICE AMONG FEMALE SEX WORKERS IN INDONESIA: A SYSTEMATIC REVIEW - Pratiwi, Donna (LIFE: International Journal of Health and Life-Sciences, 2017)
Human Immunodeficiency Virus - Acquired Immuno Deficiency Syndrome (HIV-AIDS) is one of depressing urban health encountered by the Indonesian citizen. Female sex workers are group at risk and one of the key of HIV transmission. During sexual intercourse, female sex workers didn’t pay attention to the status of customer that infected with HIV / AIDS or not. This review present to identify factors and the most influence factors in the utilization of voluntary counseling and testing (VCT) service among female sex workers in Indonesia The method use online database such as journal.fkm.ui.ac.id, journal.ugm.ac.id, ejournal.undip.ac.id, jornal.unair.ac.id, portalgaruda.id and google scholar. The keywords to search article in database online is fact or VCT or HIV-VCT or female sex workers. There are four eligible articles to review after filtered by inclusion criteria. Result from this review, factors in utilization of VCT services by female sex workers is perception of vulnerability of HIV/AIDS, perception of severity of HIV/AIDS, perception of benefits of VCT, VCT obstacle perception, motivation of VCT, knowledge of HIV/AIDS and VCT, attitude of HIV/AIDS and VCT, facilities, support by councelor, beliefs about VCT, value of knowing their HIV status and motivation to comply other’s support. The most influence factor is level of knowledge about VCT. Based on the result of this review and the description of articles, utilization of VCT Service among Female Sex Workers in Indonesia influenced by knowledge of VCT. For the next research can investigate about comparing the methods in the utilization of services in the female sex workers and other high-risk populations.